2021
DOI: 10.1101/2021.09.28.21264240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting hospital-onset COVID-19 infections using dynamic networks of patient contacts: an observational study

Abstract: Background. Real–time prediction is key to prevention and control of healthcare–associated infections. Contacts between individuals drive infections, yet most prediction frameworks fail to capture the dynamics of contact. We develop a real–time machine learning framework that incorporates dynamic patient contact networks to predict patient–level hospital–onset COVID–19 infections (HOCIs), which we test and validate on international multi–site datasets spanning epidemic and endemic periods. Methods. Our framew… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, these precautions may not be sufficient as patients may transmit the virus when they are pre-symptomatic ( Ferretti et al, 2020 ). Thus, infection prevention teams may need to identify patients at high risk of developing nosocomial Covid-19 ( Myall et al, 2021 ) if single rooms are not available for all exposed patients (e.g., in cases of overcrowding). For example, a previous study Mo et al, 2021 found that exposure to community-acquired cases who were identified and segregated or cohorted was associated with half the risk of infection compared with exposure to hospital-acquired cases or HCWs who may be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…However, these precautions may not be sufficient as patients may transmit the virus when they are pre-symptomatic ( Ferretti et al, 2020 ). Thus, infection prevention teams may need to identify patients at high risk of developing nosocomial Covid-19 ( Myall et al, 2021 ) if single rooms are not available for all exposed patients (e.g., in cases of overcrowding). For example, a previous study Mo et al, 2021 found that exposure to community-acquired cases who were identified and segregated or cohorted was associated with half the risk of infection compared with exposure to hospital-acquired cases or HCWs who may be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The executed model obtained training accuracy was 80.85% and testing accuracy was 83.84% for entropy. For the Gini index the model obtained the accuracy for training and test data was 84.08% and 84.85% respectively and the comparison was illustrated in Figure 6 and Table 2 The other metric area under the curve [25] evaluated for the given model in terms for both entropy and Gini index. AUC was constructed by plotting sensitivity against specificity.…”
Section: Resultsmentioning
confidence: 99%